Who is it? - Hunt,Roderick (China: Oxford University Press, 2012)
Who Is It? is a simple, engaging story that invites children to guess the identity of a hidden person, animal, or object through short clues and repetitive questions. Each page builds curiosity with the question (3z(BWho is it?(3y (Buntil the final reveal is shown with the help of bright illustrations. The repetitive language and clear structure make it easy for early readers to follow, while the guessing format keeps them active and excited. The story encourages observation, imagination, and prediction skills, while also building vocabulary and reading confidence.s
Who Is It? is an early reader story designed to develop curiosity, prediction skills, and word recognition in young learners. The book usually follows a simple and repetitive pattern, where children are given clues about a hidden person, character, or animal. Each page builds suspense by asking the question (3z(BWho is it?(3y (Buntil the final reveal is made. This guessing-game style structure keeps children engaged and encourages active participation as they try to predict the answer. The language is clear, repetitive, and age-appropriate, making it ideal for early readers who are just beginning to build fluency. Colorful illustrations support the text, helping children connect words with images and strengthening comprehension. The story promotes observation, attention to detail, and imagination, while also reinforcing vocabulary related to people, animals, or familiar objects. Who Is It? is well-suited for guided reading, classroom storytelling, or independent practice. Its interactive format not only builds reading confidence but also makes the learning process enjoyable for children by combining fun, suspense, and discovery.s
Keywords: Guessing game; Curiosity